1997
DOI: 10.1128/jb.179.20.6472-6479.1997
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of different segments of the par region to stable maintenance of the broad-host-range plasmid RK2

Abstract: A 3.2-kb region of the broad-host-range plasmid RK2 has been shown to encode a highly efficient plasmid maintenance system that functions in a vector-independent manner. This region, designated par, consists of two divergently arranged operons: parCBA and parDE. The 0.7-kb parDE operon promotes plasmid stability by a postsegregational killing mechanism that ensures that plasmid-free daughter cells do not survive after cell division. The 2.3-kb parCBA operon encodes a site-specific resolvase protein (ParA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…This vector is derived from the broad-host-range plasmid vector pRK310 (15), previously used for R. eutropha (7), by inserting the plasmid-stabilizing parDE region from RK2. The parDE region was obtained as a 0.7-kb ClaI-to-HindIII fragment from plasmid pRR120-0.7 (17). This plasmid was kindly provided by Don Helinski, University of California, San Diego.…”
Section: Methodsmentioning
confidence: 99%
“…This vector is derived from the broad-host-range plasmid vector pRK310 (15), previously used for R. eutropha (7), by inserting the plasmid-stabilizing parDE region from RK2. The parDE region was obtained as a 0.7-kb ClaI-to-HindIII fragment from plasmid pRR120-0.7 (17). This plasmid was kindly provided by Don Helinski, University of California, San Diego.…”
Section: Methodsmentioning
confidence: 99%
“…A high horizontal transfer rate could thus ensure the persistence of plasmids, without the need for constant or fluctuating selection for plasmid‐encoded traits, as also recently demonstrated through a newer statistical modelling approach (Ponciano et al , 2007). The key role of conjugative transfer in overall plasmid stability has also been empirically shown in liquid broth and on surfaces (Sia et al , 1995; Easter et al , 1997; Bahl et al , 2006) The question as to whether or not this horizontal spread can allow plasmids to persist as parasitic genetic elements without ever benefiting their host, is currently unanswered. Stewart and Levin (Stewart & Levin, 1977) and later studies (Bergstrom et al , 2000) reported that the transfer rates required for plasmid R1, measured in chemostats, were not high enough for the plasmid to be parasitic.…”
Section: Incp‐1 Plasmid Backbone Functionsmentioning
confidence: 99%
“…ParE, a toxin encoded on plasmid RK2 (1113), and CcdB, a toxin encoded on the F plasmid, have unrelated amino acid sequences, but they both poison DNA gyrase. CcdB and ParE are encoded adjacent to proteic antitoxins, known as CcdA and ParD, respectively.…”
Section: Introductionmentioning
confidence: 99%